2009
DOI: 10.1029/2009gl040908
|View full text |Cite
|
Sign up to set email alerts
|

A note on the altitude profiles of the electron production in the atmosphere by micrometeoroids entering it at different initial speeds

Abstract: We have extended our earlier model (Mendis et al., 2005) for the study of the dynamical, thermal and charging history of micrometeoroids entering the earth's atmosphere, by taking into account the role of sputtering, which is important for high‐speed ones. As before we confine ourselves to motion in the night side of the earth. In this short note we will not discuss these, but will confine our attention to the limited, yet important, effect of electron production in the atmosphere, by three different classes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Once again, in the interest of brevity we will restrict ourselves to vertical entry as in Mendis and Maravilla (2009), and we will consider three 'stony' micrometeoroids each of initial radius 40 μm, entering the 'top' of the atmosphere with initial speeds of 60, 30 and 15 km s −1 , representing respectively fast and average (speed) cometary micrometeoroids and a slow asteroidal one.…”
Section: The Role Of Micrometeoroid Entry Speed On the Electron Produmentioning
confidence: 99%
See 3 more Smart Citations
“…Once again, in the interest of brevity we will restrict ourselves to vertical entry as in Mendis and Maravilla (2009), and we will consider three 'stony' micrometeoroids each of initial radius 40 μm, entering the 'top' of the atmosphere with initial speeds of 60, 30 and 15 km s −1 , representing respectively fast and average (speed) cometary micrometeoroids and a slow asteroidal one.…”
Section: The Role Of Micrometeoroid Entry Speed On the Electron Produmentioning
confidence: 99%
“…They found that sputtering-associated electron production was by far the dominant one at higher altitudes, and in the process also extended the range of atmospheric ionization to significantly higher altitudes. Very recently, we (Mendis and Maravilla 2009) added sputtering to our earlier model (Mendis et al 2005), taking into account the velocity dependence of the yield, as opposed to a constant one as assumed by Brosch et al (2001), and ran it for an initial speed of entry of 60 km s −1 . Continuing to use the 'free-molecular domain' approach, we used a much smaller initial size (40 μm, corresponding to a small micrometeoroid, instead of the large value of 20 cm, used by previous authors).…”
Section: Electrical Charging and Electron Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sputtering process can result in nonnegligible meteoroid mass loss and the production of ionization at much higher altitudes than those associated with thermal ablation only [Rogers et al, 2005]. Furthermore, a recent numerical simulation study on the electron production by Mendis and Maravilla [2009] highlighted the importance of physical sputtering as a dominant process for large and fast meteoroid at high altitudes. Our own numerical simulations of meteoroid ablation for a speed of 60 km s À1 with diameters of 1 mm and 1 cm indicate that sputtering can produce significant amounts of plasma up to 10 12 electrons m À1 and 10 14 electrons m À1 , respectively (J.…”
Section: 1002/2014gl061478mentioning
confidence: 99%